From the New Deal to the New Right : race and the southern origins of modern conservatism - Lowndes, Joseph E., 1966- (Yale University Press, 2008)
The role the South has played in contemporary conservatism is perhaps the most consequential political phenomenon of the second half of the twentieth century. The region's transition from Democratic stronghold to Republican base has frequently been viewed.